Insignificant others : a novel - Jio, Sarah (William Morrow, an imprint of HarperCollins Publishers, 2025)
"From New York Times bestselling author Sarah Jio comes an escapist timeslip contemporary book club novel following a young woman stuck in a "time loop" of one-day relationships with romantic partners from her past, perfect for readers of Rebecca Serle's In Five Years and Josie Silver's One Day in December. "An ingenious and heartfelt love story. I absolutely adored this novel!" (Emily Giffin, #1 New York Times bestselling author of The Summer Pact) What if you could have a second chance to say "yes" to the one who got away? Lena Westbrook, a perfectionist and workaholic, has carefully planned and orchestrated every detail of her life. So when her boyfriend of two years breaks up with her on the night she expects him to propose, she's heartbroken and confused. Lena flees to her beloved aunt's home on Seattle's picturesque Bainbridge Island to lick her wounds and recalibrate. That night, she falls asleep in the guest house. But when she awakens the next morning, she's no longer in a cottage nestled on the Puget Sound, but rather in a chic Parisian apartment--wearing an expensive silk nightgown in bed with a handsome French man who seems to think that Lena is his wife. From the elegant neighborhoods of Paris to the charming landscape of Kinsale, Ireland, to the sparkling skyline of New York City, and many other unexpected destinations in between, each time Lena awakens, she finds herself somewhere else with someone else. In each experience, she's given a glimpse of what life might have looked like had she chosen the "road not taken." And as she becomes more clear-sighted about her past decisions, Lena begins to wonder, were any of these former romantic encounters actually . . . significant? Marrying the wish-fulfilling romance of Emily in Paris with the high-concept premise of Groundhog Day, Insignificant Others is a lively, surprising, and enchanting novel that explores the relatable and resonant "what ifs" of life, but most especially, love"--